The working class of Paraná in the documents of National Information Service (1964-85) (Research, Society and Development, 2020)
This paper aimed to analyze the configuration of Paraná’s working class during the period of Brazilian military dictatorship (1964-1985) from the investigative records of National Information Service (SNI). It was sought to elucidate the ideological perspectives that passed through the positions of the subjects and political organizations attached with workers, as well the information agent’s ideological foundation for the developing of persecutory actions against left groups. The documents from SNI were utilized as research sources, being approached by the lukácsians perspective of historical-dialectical materialism, apprehending ideologies as products of material conditions from concrete reality. The political-ideological divergences between Paraná’s rural and urban workers became evident, especially when it comes to questions about syndical organizations and Political Parties affiliation. Furthermore, it was also indicated the gradual tendency of adequation to immediatist reformism assumed by a considerable parcel from Paraná’s working class during the years of Brazilian political opening process (1975-1985).